‘Collectivism’ and Innovation: Small and medium-sized enterprises as local/rural industry in some East Asian countries - Tomoko Oikawa (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2015)
Small and medium-sized enterprises (SMEs hereafter) in the local districts in Southeast Asian countries, Thailand, Indonesia and Japan are explored. The aim is to show how ‘collectivism’ in these Asian countries is linked with innovation in rural/local industry. ‘Collectivism’ is an abstract concept itself. The exploration of community-based ‘collectivism’ in actuality in these countries shows that ‘collectivism’ is the dynamic of innovation to fight against economic difficulties, depopulation and poverty in rural/local district. The main focus is on ‘one village, one product’ movement in Japan and Thailand. Indonesia is an interesting case of innovation in terms of community-based industry. In the case of Japan, other rural/local movement among SMEs is introduced in relation to community-based collectivism and innovation. The paper explores the issues why things were, how they were, how they got to be that way and what was making them change. For this a historical, political economy, and anthropological perspective is necessary. The main findings are: 1. ‘Collectivism' is the inner dynamic of innovation in rural/local industry in these Asian countries. 2. Community-based ‘collectivism’ as solidarity and cooperative capability is the foundation of innovation. 3. SMEs as rural/ local industry as such could be gathering momentum in these countries. 4. These rural/local industries tend to be self-reliant and sustainable.